Effect of Porous Layer on Oxygen Semi Permeation and Surface Exchange of CaTi0.9Fe0.1O3-δ Membranes. (26th April 2016) - Salles, Corinne; Steil, M. C.; Fouletier, Jacques; Marinha, Daniel
Abstract : Oxygen transport membranes are dense ceramic oxides that allow oxygen diffusion along a chemical potential gradient. CaTi0.9 Fe0.1 O3−δ (CTF) exhibits an interesting tradeoff between performance and stability; despite a lower oxygen flux, it exhibits a superior thermal, mechanical, and chemical stability. To optimize the performance of CTF, it is important to establish the rate-limiting step of oxygen transport mechanism, either surface oxygen exchange reactions, or bulk diffusion. We prepared CTF membranes with and without a porous layer. The limiting step was determined using the ratio between chemical potential drop of oxygen near the surface and across the bulk. We find that bare CTF membranes exhibit a mixed-control below 750 °C, changing to a bulk-limited process with increasing temperature. The porous layer mitigates surface limitation and increases the flux by 35% at lower temperature.